Mobilizing national identities: from the Gas War to La Haya - Pennycook Castro, Andrés (Acta Bioethica, 2013)
The complex values and social perceptions called "Bolivian mediterrainity" is one of the political discourses with more presence in Bolivian national identity. Political mobilization of this discourse has played an important role both for the protest movement against the construction of a gasoduct to Chile (2000-2005) and for current Bolivian foreign policy. The article studies the causal mechanisms underlying such mobilization and formulates some inferences on bilateral political scenarios from a liberal perspective.